Exploration of Material and Medicinal Properties of Plant Species from KSAFTER Site, Putalibazaar-2, Syangja, Nepal - Parajuli, D; Paudel, B; Pokhrel, Subash; Lamichhane, Nabin; Parajuli, S; Parajuli, N (Pragya Darshan प्रज्ञा दर्शन, 2025)
The present study explores the material and medicinal properties of selected plant and moss species from the KSAFTER site (Kushechaur Simriklek Agrimed Forest Tourism Education and Research), located in Putalibazaar-2, Syangja, Nepal. Situated in a transitional ecological zone ranging from 800 to 1,700 meters above sea level, this region supports a diverse range of flora with significant but underdocumented biofunctional potential. Seven representative species, Cornus sericea, Remusatia vivipara, Coelogyne ochracea, Dicliptera chinensis, Parmotrema perlatum, Hedwigia ciliata, and Amblystegium serpens, were studied for their traditional medicinal uses and contemporary relevance in material science. Field surveys, herbarium verification, and literature-based analyses revealed multifunctional applications: from antimicrobial, anti-inflammatory, and detoxifying effects to their roles in natural dye production, bioadhesives, phytosorption, and eco-friendly composites. Notably, moss species demonstrated high potential in biomonitoring and bioremediation due to their structural traits and pollutant absorption capacity. This interdisciplinary research underscores the ecological, medicinal, and industrial value of native plant biodiversity, advocating for the sustainable utilization, conservation, and further scientific investigation of Nepal’s botanical resources.